Analisis uso excesivo de poder en los gobiernos regionales en el marco de la decentralización en los ulitmos años - ESCATE PECHO, JOSE HIPOLITO (2021)
As is known, there is an 84% percentage of Peruvians who consider that our leaders act to benefit only small interest groups, and a minimum percentage of 13% assume that they act to strengthen the people. ”We analyze that the reduction of the poverty gap, the main objective of the Decentralization Law, is hampered by its authorities, which means that the public policies created for this purpose are not being complied with; The Comptroller's Office, PCM, MEF, agree that the lack of tools for better control causes corruption to increase. The judiciary in crisis negotiating freedom and impunity with the highest bidder. We humbly propose the creation of the CODECIDE Decentralized Citizen Defense Council. Keywords: Judicial, Government, Abuse of power, corruption, mismanagement, impunity, control mechanisms, embezzlement.